(untitled) (Tribhuvan University Journal of Microbiology, 2022)
Objectives: To understand microbiological and physico-chemical quality of drinking water in Bharatpur metropolis. Methods: In a cross-sectional study, a total of 500 water samples (200 Municipal-supplied tap water, 200 hand-pump water and 100 open-well water) were collected from Bharatpur and processed for the investigation of physico-chemical and microbiological parameters. Physico-chemical parameters were analyzed by using an ENPHO water kit. The pH, arsenic and free residual chlorine (FRC) values of all the samples were within Nepal Drinking Water Quality Standard (NDWQS) 2062, whereas the concentrations of total hardness, ammonia, iron and nitrite didn’t meet the recommended limit in some of the samples. For bacteriological testing, membrane filtration (MF) technique was employed. Results: Out of the total 500 samples, 42.8% (214/500) were coliform positive. Open well water (57%) showed the highest prevalence of coliforms followed by hand-pump water (43.0%) and municipal tap water (35.5%). The occurrence of coliform in water was found to be associated with the proximity of latrines/cowsheds from the source of water (p<0.05). On antibiotic sensitivity testing (AST) of the coliforms, Gentamicin was the most effective antibiotic whilst Ampicillin was the least effective. A higher incidence of multi-drug resistant (MDR) isolates was observed with Citrobacter spp. 46.5% (60/129) followed by E. coli 11.4 % (7/61). Conclusion: None of the Klebsiella spp. isolates were MDR. Regular monitoring of water quality parameters should be done by the concerned authorities and stakeholders of the Metropolis to ensure the quality of drinking water to the city-dwellers.